Radiographic assessment of photodynamic therapy as an adjunctive treatment on induced periodontitis in immunosuppressed rats - Leandro Araújo Fernandes; Thiago Marchi Martins; Juliano Milanezi de Almeida; Letícia Helena Theodoro; Valdir Gouveia Garcia (University of São Paulo, 2010)
OBJECTIVE: The aim of this study was to assess radiographically the effect of photodynamic therapy (PDT) as an adjunctive treatment to scaling and root planing (SRP) on induced periodontitis in dexamethasone-induced immunosuppressed rats. MATERIAL AND METHODS: The animals were divided into 2 groups: ND group (n=60): saline treatment; D group (n=60): dexamethasone treatment. In both ND and D groups, periodontal disease was induced by the placement of a ligature in the left first mandibular molar. After 7 days, ligature was removed and all animals received SRP, being divided according to the following treatments: SRP: saline and PDT: phenothiazinium dye (TBO) plus laser irradiation. Ten animals per treatment were killed at 7, 15 and 30 days. The distance between the cementoenamel junction and the height of the alveolar bone crest in the mesial surface of the mandibular left first molars was determined in millimeters in each radiograph. he radiographic values were analyzed statistically by ANOVA and Tukey's test at a p value <0.05. RESULTS: Intragroup radiographic assessment (ND and D groups) showed that there was statistically signifcant less bone loss in the animals treated with PDT in all experimental periods compared to those submitted to SRP. Intergroup radiographic analysis (ND and D groups) demonstrated that there was greater bone loss in the ND group treated with SRP compared to the D group treated with PDT at 7 and 30 days. CONCLUSION: PDT was an effective adjunctive treatment to SRP on induced periodontitis in dexamethasone-induced immunosuppressed rats.